A importância do magistério extrativista para as comunidades extrativistas do Médio Xingu - CAZIMIRO, Higor Matheus Faustino (2024)
This article aims to critically evaluate the first and only pilot project that was the Extractive Magisterium, which had a significant importance for the communities and to describe the trajectory of struggles that the associations representing the Extractive Reserves of Terra do Meio and Maribel, residents and partner institutions of the communities had for this pilot project to be implemented within the UCs of Terra do Meio. The extractivist Magisterium as already mentioned previously, it was a pilot project carried out by the Federal University of Pará – UFPA, with resources from the federal government – Ministry of Education. The objective of this project was to train young extractivists to work in the classrooms of their own territories, to make up for the lack of teachers who in a certain way understood the local way of life and adapted to the context of the territory, this project had as its target audience young people from the three Land Conservation Units of the Middle, where it was conducted through the Pedagogy of Alternation.